2007
DOI: 10.1086/516583
|View full text |Cite
|
Sign up to set email alerts
|

A Wide‐Angle Tail Radio Galaxy in the COSMOS Field: Evidence for Cluster Formation

Abstract: We have identified a complex galaxy cluster system in the COSMOS field via a wide-angle tail (WAT ) radio galaxy, consistent with the idea that WAT galaxies can be used as tracers of clusters. The WAT galaxy, CWAT-01, is coincident with an elliptical galaxy resolved in the HST ACS image. Using the COSMOS multiwavelength data set, we derive the radio properties of CWAT-01 and use the optical and X-ray data to investigate its host environment. The cluster hosting CWAT-01 is part of a larger assembly consisting o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 79 publications
5
46
0
Order By: Relevance
“…Bent-tailed sources are of particular interest because they are known to inhabit galaxy clusters and can act as tracers of highredshift clusters and of cluster mergers (e.g. Blanton et al 2001;Smolčić et al 2007;Giacintucci & Venturi 2009;Mao et al 2010;Garon et al 2019, and references therein). The tails of these sources are believed to arise from a combination of the hosts moving through the intracluster medium (ICM), dragging the emission behind them, and strong cluster winds pushing the tails away from their hosts.…”
Section: Narrow and Wide Angle Tail Sourcesmentioning
confidence: 99%
“…Bent-tailed sources are of particular interest because they are known to inhabit galaxy clusters and can act as tracers of highredshift clusters and of cluster mergers (e.g. Blanton et al 2001;Smolčić et al 2007;Giacintucci & Venturi 2009;Mao et al 2010;Garon et al 2019, and references therein). The tails of these sources are believed to arise from a combination of the hosts moving through the intracluster medium (ICM), dragging the emission behind them, and strong cluster winds pushing the tails away from their hosts.…”
Section: Narrow and Wide Angle Tail Sourcesmentioning
confidence: 99%
“…Previous studies indicated that bent-double radio sources are associated with galaxy clusters (Blanton et al , 2001(Blanton et al , 2003aSmolčić et al 2007;Kantharia et al 2009;Giacintucci & Venturi 2009;Oklopčić et al 2010). Identifying these sources in radio catalogs and then searching for optical counterparts can define a sample of radio-selected galaxy clusters.…”
Section: Selecting Radio Sourcesmentioning
confidence: 99%
“…Several previously unobserved clusters have been actually identified thanks to the detection of tailed sources (e.g. Blanton et al 2003;Smolčić et al 2007;Giacintucci & Venturi 2009;Kantharia et al 2009;Mao et al 2010).…”
Section: Introductionmentioning
confidence: 99%